Penyelenggaraan Layanan Terapi Sel Punca Di Indonesia Ditinjau Dari Perspektif Bioetika - Erawati, Lusy (Magister Ilmu Hukum - Universitas Hang Tuah, 2024)
Degenerative diseases are currently the biggest cause of death in the world. Stem cells which have the ability to regenerate cells are the latest breakthrough for therapy of this disease. Stem cells use cells that come from humans, so they are fraught with ethical issues. Bioethics is a science that evaluates moral actions or the application of ethics based on scientific analysis of biology, medicine and technology for the maintenance of human health. The aim of this research is to analyze the implementation of stem cell therapy services in Indonesia from a bioethical perspective. The research methods used are normative juridical and statutory approaches, as well as conceptual approaches. The results of this research are that the provision of stem cell therapy services in Indonesia should follow ethical principles: it can only be done if it is proven to be safe, it is prohibited for reproductive purposes, it cannot come from embryonic cells, it must be sourced from humans, it cannot be bought and sold, and it is carried out by qualified medical personnel. competent. The obstacle to providing stem cell services in Indonesia is that the facilities, human resources and government regulations are not yet complete, so that many uses of stem cells are not in accordance with ethical issues and applicable regulations.